IMPORTANCE OF ADLERIAN LIFESTYLE PERSONALITY ATTRIBUTES FOR BODY MASS INDEX AMONG WOMAN - Gaube, Justina; Kern, Roy Max (European Scientific Journal, ESJ, 2015)
A number of researchers have suggested associations between personality attributes and weight issues. Nevertheless there is no clear explanation of the relationship of personality and weight control. This study investigated the impact of Adlerian Lifestyle personality attributes as it relates to Body Mass Index (BMI) among women. The study consisted of 772 Lithuanian woman who completed online instruments that included the Lithuanian version of the Basic Adlerian Scales of Interpersonal Success - Adult form (BASIS-A)Inventory and questions that assessed height, weight, and behavioral variables such as eating habits, physical activity and other weight control activities. The results indicated significant higher scores of Belonging/Social Interest, Taking Charge and Striving for Perfection in the group of women with elevated BMI in compare to normal weight. Significant predictive value of Going Along, Taking Charge and Being Cautions personality attributes together with some other behavioral and biological variables for BMI was revealed. The authors suggested practical implications and guidelines for practitioners, health professionals, and consultants.